2015
DOI: 10.1210/jc.2015-1734
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 Activates Noncanonical Wnt Signaling and Inhibits Aldosterone Production in the Human Adrenal

Abstract: Context:Aldosterone synthesis and cellularity in the human adrenal zona glomerulosa (ZG) is sparse and patchy, presumably due to salt excess. The frequency of somatic mutations causing aldosterone-producing adenomas (APAs) may be a consequence of protection from cell loss by constitutive aldosterone production.Objective:The objective of the study was to delineate a process in human ZG, which may regulate both aldosterone production and cell turnover.Design:This study included a comparison of 20 pairs of ZG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 39 publications
3
47
2
Order By: Relevance
“…This signaling appeared to inhibit aldosterone production and cell renewal and induce apoptosis (Shaikh et al 2015). These findings are in stark contrast to the data presented in this study.…”
Section: Resultscontrasting
confidence: 99%
“…This signaling appeared to inhibit aldosterone production and cell renewal and induce apoptosis (Shaikh et al 2015). These findings are in stark contrast to the data presented in this study.…”
Section: Resultscontrasting
confidence: 99%
“…This surprising finding, together with their absence from upregulated genes in rodent ZG 26 and patchiness of aldosterone synthase in human adrenal, was interpreted as an adaptive mechanism to high-salt intake in Western diet. 20,21 NEFM encodes one of the subunits forming the neurofilament, the type IV intermediate filament of mature neurons, one of the most abundant proteins in the nervous system. Neurofilament subunits perform extracytoskeletal roles in the neuronal synapses as receptor-interacting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 NEFM is also a biomarker for the wild-type, ZG-like subtype of APAs; compared with these, it was 4-fold downregulated in KCNJ5 mutant, ZF-like APAs. 22 We hypothesized that NEFM plays a role in regulating human ZG endocrine function through a similar relationship with D1R as described in the nervous system.…”
Section: August 2017mentioning
confidence: 99%
“…A transcriptome analysis of laser capture microdissected ZG and ZF cells from adrenal cortex adjacent to APA or pheochromocytoma showed that expression of LGR5 was 25-fold greater in ZG than in ZF and was the ‘top hit’ among 213 over-expressed genes in ZG compared to ZF. 50 A radial streaking of LGR5 into ZF was observed in some serial sections, presumably reflecting the centripetal migration of ZG cells during development. 50 Expression of the gene coding for the LGR5 cognate ligand R-spondin-3 (RSPO3) was also up-regulated 5-fold in ZG compared to ZF.…”
Section: Lgr5 Suppresses Cyp11b2 In Apamentioning
confidence: 94%